TECHNOLOGIES FOR IMPROVING PROFESSIONAL COMPETENCE IN STUDENTS THROUGH PREPARATION FOR PUBLIC SPORTS HEALTH ACTIVITY (Academia Science Repository, 2023)
This article discusses the importance of the professional competence of the pedagogue in preparing students for public sports health activities. It is also mentioned about the content of their activities.